The effects of extrusion on the content and properties of dietary fibre components in various barley cultivars. (March 2016) - Honců, I.; Sluková, M.; Vaculová, K.; Sedláčková, I.; Wiege, B.; Fehling, E.
Abstract: Wholemeal flour from five Czech spring barley materials was processed in a single-screw extruder at 130 °C, addition of 20% water and a screw speed of 220 rpm. Two barleys (AF Cesar, AF Lucius) were hulless cultivars with a standard starch composition, while three barleys (KM 2624, KM 2460-1, KM 2460-2) were hulled waxy lines. The effect of extrusion on content of different dietary fibre fractions was determined. Also the changes of the molar mass of β-glucan were studied. Regardless of the barley genotype (standard starch or waxy), the extrusion had no significant effect on arabinoxylan content. A significantly higher beta-glucan and soluble dietary fibre content in barley cultivars with standard starch composition was observed after extrusion. The content of insoluble dietary fibre decreased significantly in all extruded flours. The molar mass of water-extractable beta-glucan increased independently of the barley variety after extrusion. But the increase in beta-glucan extractability due to extrusion was not observed. Highlights: β-glucan content increased in standard barley materials after extrusion. The molar mass of barley β-glucan increased after extrusion. Increase in β-glucan extractability due to extrusion was not observed.